Differences in gestational weight gain between pregnancies before and after maternal bariatric surgery correlate with differences in birth weight but not with scores on the body mass index in early childhood. Issue 6 (11th December 2013) - Berglind, D.; Willmer, M.; Näslund, E.; Tynelius, P.; Sørensen, T. I. A.; Rasmussen, F.
Summary: Background: Large maternal gestational weight gain (GWG) is associated with increased birth weight and increased risk of obesity in offspring, but these associations may be confounded by genetic and environmental factors. The aim was to investigate the effects of differences in GWG in all three trimesters on differences in birth weight and in body mass index (BMI) scores at 4 and 6 years of age, within siblings born before and after bariatric surgery. Method: Women with at least one child born before and one after bariatric surgery were identified in national Swedish registers. Series of weight (and height) measurements were collected from antenatal medical records, with data on the nearest pregnancies before and after bariatric surgery. Results: The age‐adjusted means of pre‐ and post‐operative GWG of 124 women were 11.3 (standard deviation [SD] 7.2) and 8.3 (SD 6.4) kg, respectively ( P = 0.01). Adjusted fixed effects regression models showed positive associations of differences in mean total GWG with differences in siblings' birth weight, 0.023 kg per 1‐kg greater weight gain (95% confidence interval [CI]: 0.014–0.069) and for second trimester 0.53 kg for each 1‐kg greater weight per week (95% CI: 0.32–1.61), whereas no associations were found with BMI in pre‐school age. Conclusion: This study showed positive associations between differences in total and second trimester maternal GWG and differences in children's birth weight, but no association with BMI scores in pre‐school age. Maternal genetic, social and lifestyle factors fixed from one pregnancy to the next were taken into account in the analyses by the study design.